Hydrodynamics and mass transport in wall tube and microjet electrodes. Simulation and experiment for micrometer-scale electrodes - Melville, J; Coles, B; Compton, R; Simjee, N; Macpherson, J; Unwin, P (2003)
Mass transport to micrometer-sized electrodes in a microjet (wall-tube) electrode configuration is examined experimentally and through finite element modeling. Electrochemical imaging experiments reveal that local mass transport is highly sensitive to the lateral position of the nozzle with respect to the electrode. When these two components are arranged coaxially, there is a pronounced minimum in the mass transfer rate to the electrode, as determined from transport-limited current measurements. Small lateral displacements of the nozzle from the coaxial position lead first to an increase in mass transport, with the current reaching a maximum at a displacement of around one nozzle radius (50 μm). For larger lateral displacements of the nozzle from the coaxial position, the limiting current gradually decreases with increasing distance. The implications of these observations for practical applications of the microjet electrode are considered. Voltammetric measurements on the oxidation of IrCl63- in aqueous solution, with the electrode and nozzle coaxial are shown to be in good agreement with simulation of mass transport. Increasing the solution viscosity dramatically decreases mass transport to the electrode, with the reduction in the diffusion coefficient of the redox species as the major factor.